1994
DOI: 10.1080/09541449408406523
|View full text |Cite
|
Sign up to set email alerts
|

Violations of procedure invariance in preference measurement: Cognitive explanations

Abstract: A violation of procedure invariance in preference measurement is that the predominant or prominent attribute looms larger in choice than in a match ing task. In Experiment 1, this so-called prominence effect was demonstrated for choices between pairs of options, choices to accept single options, and preference ratings of single options. That is, in all these response modes the prominent attribute loomed larger than in matching. The results were replicated in Experiment 2, in which subjects chose between or rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…First, it predicted a prominence effect in both choice and preference rating judgment. As revealed by previous research (Fischer & Hawkins, 1993;Montgomery et al, 1994;Selart et al, 1994), an effect was found also for preference ratings. In these studies, a large variety of problems were used.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…First, it predicted a prominence effect in both choice and preference rating judgment. As revealed by previous research (Fischer & Hawkins, 1993;Montgomery et al, 1994;Selart et al, 1994), an effect was found also for preference ratings. In these studies, a large variety of problems were used.…”
Section: Discussionsupporting
confidence: 59%
“…In choice tasks subjects placed more weight on this attribute than they did in a matching task in which they were required to make the two options equally attractive. Subsequently, this "prominence" effect has been replicated by Montgomery, Gärling, Lindberg, and Selart (1990); Montgomery, Selart, Gärling, and Lindberg (1994); and Selart, Montgomery, Romanus, and Gärling (1994).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…According to the prominence effect, Jane would, out of two alternatives, choose the alternative that is better on the more important attribute but worse on less important attribute, although the two alternatives have been matched to be equal in attractiveness. Similarly, Montgomery and colleagues found that the prominence effect takes place not only in choices but also in attractiveness evaluations (Montgomery, Selart, Gärling, & Lindberg, 1994;Selart, Gärling, & Montgomery, 1998;Selart, Montgomery, Romanus, & Gärling, 1994). The prominence effect implies that the more important attributes will loom larger in both choices and attractiveness evaluations compared to matching tasks.…”
Section: Something Borrowedmentioning
confidence: 99%